Anglicyzmy w artykułach dziennikarzy modowych a kryteria poprawności językowej - Kaczmarek, Anna (Poznańskie Spotkania Językoznawcze, 2014)
The article deals with the subject of expansive borrowings from English, encountered in the texts of fashion journalists published in the pages of women’s magazines. The Anglicisms in question have been characterized in confrontation with the criteria of evaluation of linguistic innovation used today by normativists, namely: the criterion of self-sufficiency, language economy and also the functional, visual and aesthetic criteria. The analysis of this lexis renders possible its evaluation with regard to usefulness in the Polish language, but also makes it possible to formulate conclusions whether we can talk today about the process of creation of a professional jargon of fashion journalists.